Analisis Sensitivitas Model SEIV pada Kasus Penularan Penyakit Polio - Angelika, Venthy; Harianto, Joko (Jurnal Fourier, 2023)
The trend of polio transmission cases until 2023 is still fluctuating and does not tend to decrease monotonically. This incident is important to discuss, especially about the factors that influence cases of polio transmission. One of the studies used to describe the incidence of polio transmission is through mathematical model analysis. One of the mathematical models used to represent the incidence of polio transmission is a dynamic model with the Susceptible-Exposed-Infected-Vaccinated (SEIV) compartment. The SEIV model analyzed in this study involves seven parameters. If the value of each parameter fluctuates, it will affect cases of polio transmission. Therefore, this research aims to analyze the influence of each parameter in the SEIV model on cases of polio transmission. The method used in this research is the literature study method. Secondary data in this study was used to create a SEIV model simulation. The findings of this research are that two parameters have the greatest influence on cases of polio transmission. The infection transmission rate parameter is the most influential parameter in terms of increasing cases of polio transmission because the sensitivity index value is the highest among the other six parameters. Meanwhile, the natural death rate parameter is the parameter that has the most influence on reducing cases of polio transmission. This is because based on the sensitivity index value, the death rate parameter has the lowest sensitivity index value among the other six parameters.